Incidental multiple myeloma in a patient with neuroretinitis: a case report - Taesung Joo; Tae Gi Kim; Sang Woong Moon (BMC Ophthalmology, 2023)
Abstract Background Neuroretinitis is classically defined as a clinical triad of unilateral, painless vision loss, accompanied by optic disc edema and characteristic macular star formation. The causes of neuroretinitis can be categorized as infectious, non-infectious, and idiopathic, therefore differential diagnosis and careful evaluation are required, owing to the various etiologies and masqueraders. Case presentation A 54-year-old woman presented to the clinic with blurred vision in both eyes. A complete ophthalmic examination revealed optic disc edema with blurred margins and macular exudates, intraretinal edema in the temporal peripapillary area, and subretinal fluid with neurosensory retinal detachment in the macular area. Systemic laboratory investigations showed no signs of infection or inflammation. However, bone marrow suppression was suspected based on the results of the complete blood count test, and the patient was diagnosed with multiple myeloma. Conclusion Although neuroretinitis is rarely accompanied by hematological malignancy, it is important to be mindful of the latter because ophthalmic manifestations are a common feature of hematological malignancies and lesions occur in nearly every ocular structure.